Factors Influencing Purchase Intention Towards Private Label Brand Among Undergraduate Students - Yan, Nor Syaida; Ahmad, Nurazwa; Abu Seman, Noor Aslinda (Research in Management of Technology and Business, 2025)
Numerous brands have recently entered the market with the potential to persuade customers to purchase the chosen goods. Nonetheless, before making a purchase, customers constantly take into account a particular factor. Finding the most important element influencing purchase intention towards private label brands (PLBs) is the main goal of this study. The second goal is to ascertain how perceived price, quality, risk, and packaging relate to private brands. A self-administered questionnaire was given to UTHM students in order to evaluate the hypothesis, and 220 of them completed it, yielding a 58.7% response rate. Multiple linear regression analysis, Pearson correlation, and descriptive analysis were then performed on the data using the Statistical Package for the Social Sciences (SPSS). The findings indicate that the primary determinant of purchase intention for private label brands is perceived price. Every element demonstrates a strong positive correlation with the intention to buy. Price, quality, risk, and packaging characteristics account for 42.3% of the variance in private label brand purchase intention, according to the R-squared value of 0.423. With a significant value of p